Why are you so scared? : a child?s book about parents with PTSD - Andrews, Beth; Kirkland, Katherine (Magination Press, 2012)
Introduces post-traumatic stress disorder and explains why it can occur in family members, its symptoms, and how to live with an individual affected by PTSD